(untitled) (Journal of Laboratory Animal Science, 2024)
India is one of the countries which have oldest regulations for animal welfare and experimentation. The Committee for the Purpose of Control and Supervision of Experiments on Animals (CPCSEA) was constituted by the Government of India, way back in 1968 under chapter IV of the Prevention of Cruelty to Animals (PCA) Act, 1960 to oversee the animal experiments and welfare.